2018
DOI: 10.4103/ijmr.ijmr_854_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between liquid-based cytology & conventional Pap smear for cytological follow up of treated patients of cancer cervix

Abstract: Background & objectives:Cancer cervix is one of the most common forms of genital malignancy among Indian women. Recurrence is seen in a significant number of cases. The conventional cervical smear technique has inherent problems and screening and interpretation errors. This study was undertaken to assess the efficacy of liquid-based cytology (LBC) as a method for cytological follow up and detection of recurrence in treated cases of cancer cervix and to compare it with conventional Pap smear technique to find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 17 publications
(21 reference statements)
2
11
0
2
Order By: Relevance
“…WDPV as a presenting complaint was also seen in studies done by Khamankar S et al, 13 Sharma J et al, 14 Sherwani RK et al 15 and Singh A et al 16 This study showed more satisfactory smears in LBC( 95% ) than in CPS (92%) similar to Hegde V et al 17 (PAP34% LBC67%), Sherwani R K et al 15 Cellular overlapping, architectural change and cellular morphological change in our study was more in CPS than LBC similar to Kavatkar et al, 23 Nandini N M et al 21 and Hegde et al 17 Strander et al 24 and Kirschner B et al 25 also showed more number of unsatisfactory smears in CPS than LBC. Cases diagnosed with NILM were more in LBC (55.4%) as compared to CPS (42.9%) in this study similar to Singh V B et al, 26 Singh U et al 27 and Dhananjaya C et al 18 However studies done by Stabile S et al 28 and Beerman H et al 29 reported more number of NILM cases in CPS as compared to LBC. LSIL cases were equal in PAP and LBC in the present study and study done by Sherwani et al 15 While studies done by Budak et al, 12 Beerman et al, 29 Stabile S et al, 28 Strander et al, 24 Longatto-Filho A et al 19 and Singh U et al 27 observed more cases of LSIL in LBC as compared to CPS.…”
Section: Discussionsupporting
confidence: 83%
“…WDPV as a presenting complaint was also seen in studies done by Khamankar S et al, 13 Sharma J et al, 14 Sherwani RK et al 15 and Singh A et al 16 This study showed more satisfactory smears in LBC( 95% ) than in CPS (92%) similar to Hegde V et al 17 (PAP34% LBC67%), Sherwani R K et al 15 Cellular overlapping, architectural change and cellular morphological change in our study was more in CPS than LBC similar to Kavatkar et al, 23 Nandini N M et al 21 and Hegde et al 17 Strander et al 24 and Kirschner B et al 25 also showed more number of unsatisfactory smears in CPS than LBC. Cases diagnosed with NILM were more in LBC (55.4%) as compared to CPS (42.9%) in this study similar to Singh V B et al, 26 Singh U et al 27 and Dhananjaya C et al 18 However studies done by Stabile S et al 28 and Beerman H et al 29 reported more number of NILM cases in CPS as compared to LBC. LSIL cases were equal in PAP and LBC in the present study and study done by Sherwani et al 15 While studies done by Budak et al, 12 Beerman et al, 29 Stabile S et al, 28 Strander et al, 24 Longatto-Filho A et al 19 and Singh U et al 27 observed more cases of LSIL in LBC as compared to CPS.…”
Section: Discussionsupporting
confidence: 83%
“…The advantages of liquid-based cytology include improved sensitivity and specificity since fixation is better and nuclear details are well preserved. Singh et al (2018) proved that LBC performed much better by showing more sensitivity, specificity and accuracy than the conventional method of cytology to detect recurrence of squamous cell carcinoma [15]. Abnormal cells are not obscured or diluted by other epithelial or inflammatory cells.…”
Section: Artificial Exfoliation (Surface Microbiopsy)mentioning
confidence: 97%
“…The second technique is the preferred method in private practice. There is however a significant difference in results between the two methods, with the liquid-based cytology 7,8,9 being superior to the traditional method in terms of sensitivity.…”
Section: Introductionmentioning
confidence: 99%